Perinatal palliative care: focus on comfort - McCarthy, F. T.; Kenis, A.; Parravicini, E. (Frontiers in Pediatrics, 2023)
Providing comfort while a patient is living with a life-limiting condition or at end of life is the hallmark of palliative care regardless of the patient's age. In perinatal palliative care, the patient is unable to speak for themselves. In this manuscript we will present guidelines garnered from the 15year experience of the Neonatal Comfort Care Program at Columbia University Irving Medical Center, and how they provide care for families along the perinatal journey. We will describe essential tools and strategies necessary to consider in assessing and providing comfort to infants facing a lifelimiting diagnosis in utero, born at the cusp of viability or critically ill where the burden of care may outweigh the benefit.